A world without nuclear weapons? The new charms of an old vision - Roland Hiemann; Oliver Thränert (Stiftung Wissenschaft und Politik (SWP), 2008)
A debate is underway in the United States, which has clearly met with international resonance. It resorts to an old vision: the abolition of nuclear weapons. Its initiators are anything but political outsiders: they are experienced politicians and experts, hardened by crisis. Among their number are Henry Kissinger and George P. Shultz. Their considerations are spurred by the deep crisis in which the nuclear non-proliferation regime finds itself. Should current expectations prove accurate and the 2010 review conference end in failure like its 2005 predecessor, this could trigger the collapse of the whole regime. Within a few years, one could then imagine an increasing number of states as well as non-state actors gaining access to nuclear weapons. Against this background, advocates of complete nuclear disarmament call for a radical approach. But how realistic are their proposals? And what does the debate entail for German and European policy?
Keywords: 320